Effect of Beta Vulgaris L Seed Forgiveness on Sowing Depth - A. S. Abdigapbarov; G. T. Erejepova; B. Kh. Makulbaeva (Researchparks Publishing, 2022)
The influence of planting depth on yield in the production of soup beets on saline soils in Karakalpakstan was investigated in this article. Germination of seeds sown at a depth of 3-4 cm, plant density, number of leaves, root weight, and days of vegetation before technical ripening are all preferable than alternative options, according to the results of this article's tests.